Multifunctional electrospun asymmetric wettable membrane containing black phosphorus/Rg1 for enhancing infected wound healing - Liming Zhou; Nanbo Liu; Longbao Feng; Mingyi Zhao; Peng Wu; Yunfei Chai; Jian Liu; Ping Zhu; Rui Guo (Wiley, 2022)
Abstract Bacterial infection is one of the most frequent complications in the burn and chronic wounds. Inspired by natural existing superhydrophobic surface structures, a novel asymmetric wettable membrane was prepared using the electrospinning technique for facilitating the bacteria‐infected wound healing. Herein, the prepared membrane consists of two layers: The hydrophobic outer layer was composed of poly (lactic‐co‐glycolic) acid (PLGA) and black phosphorus‐grafted chitosan (HACC‐BP), while the hydrophilic inner layer was composed by using a mixture of gelatin (Gel) with ginsenoside Rg1 (Rg1). Biological studies in vitro showed BP@PLGA/Gel (BP@BM) membrane with excellent antibacterial activity could significantly inhibit the adhesion of bacteria, and Rg1 could facilitate the migration and tube formation of human umbilical vein endothelial cells (HUVECs). Compared to Aquacel Ag dressing, the result in vivo revealed that the Rg1/BP@BM could facilitate better wound healing by triggering phosphoinositide 3‐kinase (P‐PI3K/PI3K) and phosphorylation of protein kinase B (P‐AKT/AKT) signaling pathways, upregulating Ki67, CD31, α‐SMA, and TGF‐β1, and downregulating TNF‐α, IL‐1β, and IL‐6, promoting M2 polarization (IL‐10, CD206, and Arg‐1) of macrophages, inhibiting M1 polarization (iNOS) of macrophages. These findings suggested that the asymmetric wettable membrane have the huge potential for wound healing.